A mobile application system for parking validation based on deep learning image processing / Alias Deraman and Muhammad Izz Kamaruddin - Deraman, Alias; Kamaruddin, Muhammad Izz (Faculty of Computer and Mathematical Sciences, 2023)
It was difficult to distinguish between authorized and unauthorized vehicles that were parked at parking area although it had institutions sticker. With the advent of technology today, everything can be fake. This issue can lead to problems of security and management, and the limited parking space makes it worse. Therefore, a mobile app was designed and developed to support the authority by snapping the car plate number. A deep learning algorithm be implemented to validate car identification and extract the owner details. The functionality test has been done and the system work properly. This mobile apps system can be used at any type of private car park and ca be extended to manage car reservation system.